OHS-Based Welding Training as an Effort to Increase Work Safety Skills and Awareness in the Community - Aung Ye Kyew (Collaborate, 2023)
This training is a form of community service by tertiary institutions to improve human resources quality. Through this training, the community can increase their knowledge and skills in welding by occupational safety and health (OHS) regulatory standards. This training consists of two stages: preparation and implementation of activities. The preparation stage includes the procurement of materials and guidelines for carrying out the welding process. At the same time, the activity implementation phase includes an explanation of occupational safety and health and welding training. The results of this training are expected to increase the public's knowledge and understanding of the importance of applying OHS in the welding process in the workplace.